The Effect Of Subjective Norms, Competence And Professional Code Of Ethics In Increasing Job Satisfaction Through The Mediation Of Motivation Variables In The Professional Association Of The Indonesia Architecture Link - Irma Rosalia Handayani; Rhian Indradewa (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
In an organization, employee job satisfaction is an important factor in the management of human resources so it must be optimized, because job satisfaction determines the success of the organization's strategic goals and is able to contribute economically. Job satisfaction in an organization needs to be improved considering the current level of competition which is also getting tighter, so it is quite important to conduct research on the factors that affect the job satisfaction of architects. This research aims to analyze and explain the influence of competence on architect's motivation and the influence of professional code of ethics, competence, subjective norms and architect's motivation on architect's job satisfaction. This research uses an explanatory survey method approach with a questionnaire as a primary data collection tool online through google form. The research was conducted on May 20, 2023 until the Questionnaire was distributed to 100 members of the IAI Professional Association-Indonesian Architects Association. Multivariate statistical method namely Partial Least Square-Structural Equation Modeling (PLS-SEM) was used to answer the research hypothesis. The results of the research prove that competence has a positive influence on motivation, competence has a positive influence on job satisfaction, subjective norms have a significant influence on Job Satisfaction and Motivation has a significant influence on Job Satisfaction. While the professional code of ethics does not have a significant effect on Job Satisfaction. The implications of the results of this research for the organization should be able to increase the job satisfaction of architects, that is, by increasing their competence and work motivation. Competence can be done by improving their work skills with a variety of more challenging tasks. The same goes for work motivation, such as giving wide powers to the architect to organize his work team to always coordinate well. As for the organization of IAI as a container of architects' bonds, it should be more active in socializing the public/clients, by educating them on the importance of using the services of certified or licensed architects. For IAI, it should give strict sanctions to its members who practice by violating the code of ethics of the profession of an architect.